2010
DOI: 10.1213/ane.0b013e3181d27b30
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Electroporation

Abstract: Relaxant general anesthesia is required for IRE of the liver, lung, and kidney. An electrocardiogram synchronizer should be used to minimize the risk of arrhythmias. Attention to the position of the arms is required to maximize CT scan quality but minimize brachial plexus strain. Simple postoperative analgesia is all that is required in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(57 citation statements)
references
References 10 publications
1
50
1
4
Order By: Relevance
“…[52] In addition, IRE can cause unintended injury to other structures when electrodes are placed. Ball et al [43] reported 3 instances of pneumothorax during their study. One of these cases occurred after transabdominal placement of electrodes in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[52] In addition, IRE can cause unintended injury to other structures when electrodes are placed. Ball et al [43] reported 3 instances of pneumothorax during their study. One of these cases occurred after transabdominal placement of electrodes in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac arrhythmia is also a notable serious complication from IRE due to the presence of high current close to the heart. Ventricular bigeminy, ventricular tachycardia, and atrial fibrillation were reported by Ball et al and Thomson et al [43,44] According to the study, the most serious cardiac rhythm disturbance occurred during the ablation of a very large hepatic tumor which was directly beneath the diaphragm and close to the inferior cardiac border. [43] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because cells survive these high subzero freezing temperatures, cryosurgery/PEF would retain PEFs' ability to selectively ablate only cellular membranes without affecting the extracellular matrix, when cryosurgery/PEF is used at high subzero temperatures. Another advantage of this combination may be related to elimination of certain side effects and limitations of PEF [41], [42]. The most severe side effects are arrhythmias and involuntary muscle contractions [41], [42] caused by low strength electric fields that expand beyond the PEF treatment zone.…”
Section: Resultsmentioning
confidence: 99%
“…Another advantage of this combination may be related to elimination of certain side effects and limitations of PEF [41], [42]. The most severe side effects are arrhythmias and involuntary muscle contractions [41], [42] caused by low strength electric fields that expand beyond the PEF treatment zone. The solution to arrhythmias through a synchronizer device is described in [42].…”
Section: Resultsmentioning
confidence: 99%